155k views
3 votes
Help me pleaseeeeeeeeeee

Help me pleaseeeeeeeeeee-example-1

2 Answers

3 votes
7x= -42
X= -6

6y= -42
Y= -7
User Fitsyu
by
5.5k points
3 votes
7x + 6y = -42
For this case what you should do is see the intersections with each of the axes and then join the ordered pairs.
We have then:
For the x axis:
y = 0
Substituting in the equation:
7x + 6 (0) = - 42
7x + 0 = -42
x = -6
For the y axis:
x = 0
Substituting in the equation:
7 (0) + 6y = -42
0 + 6y = -42
y = -42 / 6
y = -7
We graph the ordered pairs:
(x1, y1) = (- 6, 0)
(x2, y2) = (0, -7)
Answer:
See attached graph.
Help me pleaseeeeeeeeeee-example-1
User Arkanoid
by
5.8k points